Long-term effects of a protein-enriched diet on blood pressure in older women - Hodgson, J.; Zhu, K.; Lewis, J.; Kerr, Deborah; Meng, Xingqiong; Solah, Vicky; Devine, A.; Binns, Colin; Woodman, J.; Prince, R. (Cambridge University Press, 2012)
Short-term randomised, controlled trials have found that dietary protein relative to carbohydrate can reduce blood pressure. Our objective was to investigate the effects on blood pressure of an increase in protein intake from whey over 2 years in women aged over 70 years. From the general population, 219 women aged between 70 and 80 years were recruited to a 2-year randomised, double-blind, placebo-controlled parallel-design trial: 181 women completed the trial to the end of year 2. Participants were randomly assigned to consume a daily whey protein-based beverage (protein) or an energy-matched low-protein high-carbohydrate beverage (control). Blood pressure measurements were performed at baseline, year 1 and year 2. For protein relative to control, the estimated mean net differences in protein and carbohydrate intakes were 18 (95 % CI 13, 23) and − 22 (95 % CI − 9, − 35) g/d at year 1, and 22 (95 % CI 17, 28) and − 18 (95 % CI − 6, − 31) g/d at year 2. Intention-to-treat analysis found no overall differences between groups in blood pressure (P>0.5). Net differences in systolic and diastolic blood pressure were – 2.3 (95 % CI – 5.3, 0.7) and – 1.5 (95 % CI – 3.6, 0.6) mmHg at year 1, and 1.6 (95 % CI – 1.5, 4.7) and 0.3 (95 % CI – 1.9, 2.4) mmHg at year 2. Similar differences in systolic and diastolic blood pressure at years 1 and 2 were observed with per-protocol analysis. Therefore, the present study did not provide evidence that a higher whey protein intake in older women can have prolonged effects on blood pressure.